1991
DOI: 10.1161/01.cir.84.3.1364
|View full text |Cite
|
Sign up to set email alerts
|

Proarrhythmic response to sodium channel blockade. Theoretical model and numerical experiments.

Abstract: Background. The use of flecainide and encainide was terminated in the Cardiac Arrhythmia Suppression Trial because of an excess of sudden cardiac deaths in the active treatment group. Such events might arise from reentrant rhythms initiated by premature stimulation in the presence of anisotropic sodium channel availability. Drugs that bind to sodium channels increase the functional dispersion of refractoriness by slowing (a result of the drug-unbinding process) the transition from an inexcitable state to an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
4

Year Published

1993
1993
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(72 citation statements)
references
References 42 publications
3
65
0
4
Order By: Relevance
“…1,39 -41 Computer models support the hypothesis that proarrhythmic mechanisms of Na ϩ channel blockade are associated with the reduction of Na ϩ channel availability. 42 In our study, flecainide potentiated the delay of recovery from inactivation caused by IsoK ( Figure 4B). Studies in the intact EBZ preparation have shown this synergistic effect of flecainide on conduction abnormalities of this arrhythmic substrate.…”
Section: Discussionsupporting
confidence: 61%
“…1,39 -41 Computer models support the hypothesis that proarrhythmic mechanisms of Na ϩ channel blockade are associated with the reduction of Na ϩ channel availability. 42 In our study, flecainide potentiated the delay of recovery from inactivation caused by IsoK ( Figure 4B). Studies in the intact EBZ preparation have shown this synergistic effect of flecainide on conduction abnormalities of this arrhythmic substrate.…”
Section: Discussionsupporting
confidence: 61%
“…4,31,32,33 Hille,34 in his modulated receptor hypothesis explains the shift of inactivation in presence of use-dependent block of sodium currents during repetitive pulses. 35,36,37 The hypothesis predicted that the open and inactivated states of voltage gated Na channels have higher affinities toward LA drugs than that of the resting state.…”
Section: Kinetics Of Drug Bindingmentioning
confidence: 99%
“…The latter is known to facilitate reentry arrhythmias. 20 Finally, because not all cardiac APDs are identical, it is important that many potassium channels be open at the end of the action potential and early during diastole. This not only clamps the membrane potential closer to the potassium equilibrium potential but also reduces the tissue impedance, rendering activation due to current flow between cells at different potentials less likely.…”
Section: Mechanismsmentioning
confidence: 99%